OPTIMALISASI TUGAS POKOK DAN FUNGSI PENYULUH DALAM KERANGKA PELAKSANAAN UNDANG-UNDANG NOMOR 16 TAHUN 2006 - Khadijah Khairunnisa; Sapja Anantanyu; Arip Wijianto (Universitas Sebelas Maret, 2017)
This study aims to analyze the aspects of the performance of the main tasks and extension functions on institutions that have implemented and have not implemented Law number 16 of 2006. The basic method used in the research is qualitative descriptive by case study method. The location of research is the Executing Agency of Sragen Regency that already implemented Law Number 16 of 2006 and the Agricultural Service of Klaten Regency that haven’t implemented Law Number 16 of 2006. Data were obtained by interview guidance on 14 informants through observation, interview and documentation. The data analysis used is interactive analysis that consist of data reduction, data presentation and conclusion drawing. The data is validated with source triangulation and method triangulation. The results showed that the implementation of the main tasks and functions of extension on institutions that have implemented and have not implemented Law no. 16 of 2006 is the same, ie from the preparation process extension until the evaluation and reporting process. There is no difference in the two institutions in performing their main duties and functions.